Thermal stability of ionene polymers - Campos, Valquíria [UNESP]; Dweck, Jo; Nascimento, Cláudio A. O.; Tcacenco, Celize M. (Springer Nature, 2013)
Two different cationic polymers of the same chemical type and with very similar chemical structures were reacted with a natural bentonite over a wide range of polymer/clay ratios. This study involved the synthesis of cationic aliphatic ammonium polyionenes, specifically 3,6-ionene and 3,6-dodecylionene. Ionenes are ion-containing polymers that contain quaternary nitrogen atoms in the main macromolecular chain as opposed to a pendant chain. The CHN content, basal spacing, and elemental composition of each of the polymer-clay complexes were analyzed by X-ray diffraction, X-ray fluorescence, and thermogravimetry. All the polycations reacted to form interlayer complexes with clay, which displaced more Na+ and little Ca2+. Sodium and calcium were both present as interlayer cations in the clay and its complexes. The TG/DTG curves show that both polymers underwent thermal degradation in more than one stage. Specifically, 3,6-ionene was found to undergo two stages of decomposition and 3,6-dodecylionene undergo three stages. The behavior of the TG/DTG curves and the activation energy values suggest that 3,6-dodecylionene (E = 174,85 kJ mol-1) complexes have greater thermal stability than 3,6-ionene (E = 115,52 kJ mol-1) complexes. The mechanism of degradation suggests a direct interaction with the dodecyl chain containing 12 carbons, which are present in 3,6-dodecylionene but not in 3,6-ionene. © 2012 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Clay-polymer complexes; Ionenes; Smectite; Thermal analysis; Elemental compositions; Ion-containing polymers; Macromolecular chain; Mechanism of degradation; Quaternary nitrogens; Smectites; Activation energy; Bentonite; Calcium; Natural polymers; Thermoanalysis; Thermodynamic stability; Thermogravimetric analysis; X ray diffraction; Polymers